Art and architecture of Ireland : Volume IV: Architecture,1600-2000 - Loeber, Rolf; Loeber, Rolf; Campbell, Hugh; Campbell, Hugh; Hurley, Livia; Hurley, Livia; Montague, John; Montague, John; Rowley, Ellen; Rowley, Ellen; Carpenter, Andrew; Carpenter, Andrew (Royal Irish Academy, 2015)
Protagonists -- Building materials, construction and interior decoration -- Architectural styles and discourse -- Infrastructure -- Civic, institutional and military architecture -- Industrial and commercial architecture -- Ecclesiastical architecture -- Rural domestic architecture -- Urban environment and housing -- The architecture of recreation and public resort -- Heritage and conservation -- Irish architecture in the first decade of the new century.